An inequality for the minimum affine curvature of a plane curve - Yang, Yunlong (Comptes Rendus. Mathématique, 2020)
As an application of the affine curve shortening flow, we will prove an inequality for minimum affine curvature of a smooth simple closed curve in the Euclidean plane.